Raymond Williams and the politics of the Commons: the performative quality of the intellectual - Stevenson, Nick (Sage, 2017)
Much of the sociological work on intellectuals is mostly concerned with the structural role they play within society. In this respect, Raymond Williams is best understood in Gramscian (1988) terms as an organic intellectual connected to the labour movement and the working-class, seeking to criticise the dominating features of contemporary capitalism. Williams is widely seen as a post-war intellectual connected to the New Left and organised labour. Indeed Williams’s (1981) own account of intellectuals is mostly concerned with exploring the structurally conditioned class-based society disallows critical study. More recently sociological work has concentrated on the reasons behind the relative decline of intellectuals due to the dominance of think tanks, consumerism and the increasingly instrumental narrow specialisms (Furedi 2004, Misztal 2012). There is then perhaps a nostalgia for the ‘big intellectuals’ of the past who were capable of producing intellectual narratives beyond the more modest aims of contemporary knowledge producers (Bauman 1992). Whatever the contemporary insights of this view, there are limitations to the sociologically-informed, structural account of intellectual cultural production. Jeffrey Alexander (2016) has recently argued that the sociology of intellectuals needs to take a more performative turn. Instead of viewing intellectuals purely in terms of structural class relationships we need to understand their ability to produce dramatic and compelling narratives. In other words, when considering intellectuals we need to understand their ability to create exciting stories and compelling performances. Especially significant in this respect are heroic narratives and the stories of good versus evil. In other words, the performative effect of ideas is in making an impact upon society. As a Durkheimian sociologist Alexander (2016:348) is interested in how intellectuals produce ideas of the sacred and profane through the production of binary categories more generally. However Alexander (2003:228) also argues that investigating the ways in which moral categories become constructed through codes and narratives is especially important in the current setting. For example, the work by Marxist intellectuals in the past reproduced binary categories they claimed would eventually lead to the salvation of humanity. Here Alexander (2003:228) is suggesting we need to respect the power of the stories produced by intellectuals, but at the same time be cautious of their ‘totalizing conceit’. In other words, we need to recognise the reductive nature of many of these stories. Here I want to argue that Alexander’s work on intellectuals offers new possibilities for the study of intellectuals like Raymond Williams, but is sometimes (although not always) a problematic guide to the complexity of Marxist writing. As Baert and Morgan (2017:5) argue, an emphasis upon performativity can overwhelm the need to make connections between dramatised and more structural accounts. In this respect, I shall argue that beyond the performative dimensions of Williams’s writing there remain good reasons to return to his work not only within our shared neoliberal times, but in the context of the rise of radical social movements against austerity seeking to defend the commons.